A study of evaluation of chronic pain abdomen in pediatric patients by laparoscopy - Khasnis, Ravindra G.; S., Rajshankar (International Surgery Journal, 2019)
Background: Pain in abdomen of chronic nature is common in children but being so common difficult to determine the exact cause. It has been estimated that around 2-4% of all the pediatric patients attend the outpatient department are due to pain in the abdomen that is of chronic nature in children. It has been seen that routine diagnostic and therapeutic procedures fail to make a justice of the diagnosis and management for the pain in the abdomen of chronic nature. The aim was to study the role of laparoscopy in children with chronic pain abdomen. Methods: Interventional follow up study was carried out among 19 children with pain in the abdomen of chronic nature. Detailed history pertaining to pain in the abdomen, history of surgical explorations was taken. As a part of the work up of a patient the investigations were done routinely. All children were evaluated by laparoscopy. Results: Majority of the children were in the age group of 11-12 years i.e. 42.1%. Male and female children were almost equal in distribution. USG was diagnostic in 9 patients (47.36%). Laparoscopy was diagnostic in all 18 other cases (95% cases). 73.68% had not complication after the procedure. Only four patients had fever after the surgery and only one patient had wound infection. Thus, overall the laparoscopic procedure was very successful. Laparoscopy and USG were equally effective in diagnosing inguinal hernia. Conclusions: Laparoscopy had better diagnostic value compared to ultrasonography. Laparoscopic intervention was successful with minimum complications.